2013
DOI: 10.1016/j.foodchem.2013.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Study of selenocompounds from selenium-enriched culture of edible sprouts

Abstract: 12 13Selenium is recognized as an essential micronutrient for humans and animals. One of the main 14 sources of selenocompounds in the human diet is vegetables. Therefore, this study deals with the 15 Se species present in different edible sprouts grown in Se-enriched media. We grew alfalfa, lentil 16 and soy in a hydroponic system amended with soluble salts, containing the same proportion of 17 Se, in the form of Se(VI) and Se(IV). Total Se in the sprouts was determined by acidic digestion 18 in a microwave s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…On the other hand, considering alfalfa, chicory and cucumber, the Se concentration levels were comparable. 13,16,20,21,50 However, the larger the Se uptake the greater may be its influence in other nutrient absorption and it may upset the nutritional balance of the plant. Thus, for a better understanding of this influence, the results obtained for the nutrient concentrations were also evaluated by principal components analysis.…”
Section: Minerals Accumulation Pca and Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, considering alfalfa, chicory and cucumber, the Se concentration levels were comparable. 13,16,20,21,50 However, the larger the Se uptake the greater may be its influence in other nutrient absorption and it may upset the nutritional balance of the plant. Thus, for a better understanding of this influence, the results obtained for the nutrient concentrations were also evaluated by principal components analysis.…”
Section: Minerals Accumulation Pca and Theoretical Calculationsmentioning
confidence: 99%
“…The authors concluded that Se biofortification in lentil are possible to increase Se intake for Se deficient populations. Funes-Collado et al 13 considered the selenite and selenate biofortification in alfalfa, lentils and soybeans sprouts hydroponically cultivated. The results showed that the high Se fortification can damage or inhibit plant growth and that the Se content increases with the Se added and part of the inorganic Se was converted mainly to SeMet.…”
Section: Introductionmentioning
confidence: 99%
“…The speciation of Se is also greatly influenced by factors such as redox potential and pH which controls its mobility in the soil [19]. Selenium is transformed from one chemical form to another within the plant-soil environment [20]. The transformations of Se within the plant explain its metabolism and mechanisms for coping with high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ultimate source of Se in the animal and human food chain is plant available soil selenium. Plants take up Se from the soil in the form of selenite or selenate and synthesize selenoamino acids with selenomethionine (SeMet) as the primary compound [17]. In plants, SeMet represents more than 50% of the total Se [18]; the other selenocompounds in plants include Se-methylselenomethionine, selenocysteine and Se-methylselenocysteine [19].…”
Section: Selenium In the Food Chainmentioning
confidence: 99%